Effects of Acupuncture in Ischemic Stroke Rehabilitation: A Randomized Controlled Trial - Li, Lixia; Zhu, Weifeng; Lin, Guohua; Chen, Chuyun; Tang, Donghui; Lin, Shiyu; Weng, Xiaorong; Xie, Liqin; Lu, Lihong; Li, Weilin (Frontiers in Neurology, 2022)
Background: Acupuncture is a well-known treatment option for ischemic stroke recovery, but evidence of its effectiveness remains limited. This is a randomized controlled trial to evaluate the effectiveness of acupuncture treatment for ischemic stroke rehabilitation. Methods: Rehabilitation training was provided to a control group. In Acupuncture Arm 1, these acupoints were derived from the ancient books，including GV20 (baihui), GV26 (shuigou), PC9 (zhongchong), ST6 (jiache), ST4 (dicang), LI15 (jianyu), LI11 (quchi), LI4 (hegu), GB30 (huantiao), GB31 (fengshi), GB34 (yanglingquan) and GB39 (xuanzhong). In Acupuncture Arm 2, the acupoints used were GV20 (baihui), PC6 (neiguan), LI11 (quchi), LI10 (shousanli), SJ5 (waiguan), LI4 (hegu), GB30 (huantiao), ST36 (zusanli), GB34 (yanglingquan), SP6 (sanyinjiao), ST41 (jiexi) and LR3 (taichong) that were extracted from Acupuncture and Moxibustion Science. After acupuncture, the needles were left in for 30 minutes, and manually manipulated every 10 minutes. The three groups received treatment once a day, 5 times a week for 2 weeks. The primary outcome was the National Institute of Health Stroke Scale (NIHSS), and the secondary outcomes were the Barthel index (BI) and the modified Ashworth scale (MAS). Outcomes were measured in patients both before and after treatment. Results: A total of 497 patients with ischemic stroke were randomized into either Arm 1 (159 cases), Arm 2 (173 cases) or a control group (165 cases). After 2 weeks of treatment, the NIHSS scores for Arm 1 were lower than those of the control group (P = 0.017); the BI scores were higher in Arm 2 than that in the control group (P = 0.020). Additionally, there was no significant difference between Arm 1 and the control group for either the BI scores or the modified Ashworth scale scores (P > 0.05). Conclusion: The clinical efficacy of Arm 1 and Arm 2 (acupuncture groups) was superior to that of the control group, but there was no difference between the effects of the two acupuncture groups. TRIAL REGISTRATION: Chinese Clinical Trial Registry: ChiCTR-IOR-16008627, Registered 11 June 2016, http://www.chictr.org.cn/index.aspx. KEYWORDS: Acupuncture; ischemic stroke; randomized controlled trial (RCT); rehabilitation.